Non-inferiority of short-term urethral catheterization following fistula repair surgery: study protocol for a randomized controlled trial - Barone Mark A; Frajzyngier Vera; Arrowsmith Steven; Ruminjo Joseph; Seuc Armando; Landry Evelyn; Beattie Karen; Barry Thierno; Lewis Alyona; Muleta Mulu; Nembunzu Dolorès; Olupot Robert; et al. (BMC, 2012)
Abstract Background A vaginal fistula is a devastating condition, affecting an estimated 2 million girls and women across Africa and Asia. There are numerous challenges associated with providing fistula repair services in developing countries, including limited availability of operating rooms, equipment, surgeons with specialized skills, and funding from local or international donors to support surgeries and subsequent post-operative care. Finding ways of providing services in a more efficient and cost-effective manner, without compromising surgical outcomes and the overall health of the patient, is paramount. Shortening the duration of urethral catheterization following fistula repair surgery would increase treatment capacity, lower costs of services, and potentially lower risk of healthcare-associated infections among fistula patients. There is a lack of empirical evidence supporting any particular length of time for urethral catheterization following fistula repair surgery. This study will examine whether short-term (7 day) urethral catheterization is not worse by more than a minimal relevant difference to longer-term (14 day) urethral catheterization in terms of incidence of fistula repair breakdown among women with simple fistula presenting at study sites for fistula repair service. Methods/Design This study is a facility-based, multicenter, non-inferiority randomized controlled trial (RCT) comparing the new proposed short-term (7 day) urethral catheterization to longer-term (14 day) urethral catheterization in terms of predicting fistula repair breakdown. The primary outcome is fistula repair breakdown up to three months following fistula repair surgery as assessed by a urinary dye test. Secondary outcomes will include repair breakdown one week following catheter removal, intermittent catheterization due to urinary retention and the occurrence of septic or febrile episodes, prolonged hospitalization for medical reasons, catheter blockage, and self-reported residual incontinence. This trial will be conducted among 512 women with simple fistula presenting at 8 study sites for fistula repair surgery over the course of 24 months at each site. Discussion If no major safety issues are identified, the data from this trial may facilitate adoption of short-term urethral catheterization following repair of simple fistula in sub-Saharan Africa and Asia. Trial registration ClinicalTrials.gov Identifier NCT01428830.